Injection moulding of micro droplet generation thermoplastics devices - Goh, Qing Wen (2014)
Microfluidic devices have been extensively researched and developed since 1990s. It can be applied to a wide variety of processes ranging from bioprocess optimization to nanoparticle crystallization. Hence injection moulding became a popular method to fabricate thermoplastic microfluidic devices, as it is able to rapidly produce parts in large quantities.